Smart Home Monitoring Pintu Rumah Dengan Identifikasi Wajah Menerapkan Camera ESP32 Berbasis IoT - Budi Yanto; Basorudin Basorudin; Saiful Anwar; Adyanata Lubis; Karmi Karmi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
The Smart Home security system for house door locks with the face of the homeowner uses ESP32Cam as a face detection camera in case of problems that occur with a lack of home security so that criminals can break into the door of the house. So the need for a tool that can increase the security of the door so that it is not easily opened. The face protection process is in accordance with what is input to the system camera ESP32Cam; the relay automatically gives the command to open the door to the magnetic solenoid so that the door is opened. Testing tools through the method experimental (trial and error) the tool works well and helps homeowners in increasing home security by 97% suitable for use and functioning with a distance of 5-10 cm.